2017
DOI: 10.7717/peerj.3255
|View full text |Cite
|
Sign up to set email alerts
|

In silicoanalysis reveals widespread presence of three gene families, MAPK, MAPKK and MAPKKK, of the MAPK cascade from crop plants ofSolanaceaein comparison to the distantly-related syntenic species fromRubiaceae,coffee

Abstract: Mitogen-activated protein kinases (MAPKs) are an important family of genes which play roles in vital plant processes, and they also help in coping against various kinds of environmental stresses including abiotic as well as biotic factors. The advancement of genomics calls for the annotation, identification, and detailed processing of the essential gene families in plants in order to provide insights into the importance of their central roles as well as for providing the basis for making their growth vigorous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In addition, AtMPK3 from Arabidopsis thaliana is located in the cytosol nucleus [45,46]. Subcellular localization analysis of MAPK in Tobacco with the use of CELLO v.2.5 revealed that NtMPK7 was localized both in the nucleus and cytoplasm [47]. Our analysis of GhMPK3-GPF protein suggests that GhMPK3 was located in the cell cytoplasm, indicating that it may interfere with signaling pathways.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, AtMPK3 from Arabidopsis thaliana is located in the cytosol nucleus [45,46]. Subcellular localization analysis of MAPK in Tobacco with the use of CELLO v.2.5 revealed that NtMPK7 was localized both in the nucleus and cytoplasm [47]. Our analysis of GhMPK3-GPF protein suggests that GhMPK3 was located in the cell cytoplasm, indicating that it may interfere with signaling pathways.…”
Section: Discussionmentioning
confidence: 76%
“…On the basis of the increasing genome information, analyzing gene families via comparative genomics is an efficient method for modern functional genomics research ( Xu et al, 2016 ). However, unlike many other gene families, including some transcription factors and kinases ( Iftikhar et al, 2017 ; Ma et al, 2017 ; Xi et al, 2017 ), studies on the characteristics and functional analysis of the plant MTP gene family are just reported in few species recently ( Fu et al, 2017 ; Vatansever et al, 2017 ). As MTP genes have been demonstrated to participate in tolerating and transporting various heavy metals, including plant trace elements and non-essential elements ( Kim et al, 2004 ; Delhaize et al, 2007 ; Xu et al, 2009 ; Lang et al, 2011 ), they might thus play significant roles in plant mineral nutrition maintenance and resistance to stresses caused by metals.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Similar gene sets have been evolutionarily conserved among higher plants, although there are variations in gene numbers within a plant species. 2,[9][10][11] MPK3, MPK4, and MPK6 are components of the Arabidopsis MAPK cascades, which are well known for being involved in plant responses to various stimuli, including pathogenassociated molecular patterns, H 2 O 2 , cold, salt, osmotic shock, and hormones such as ABA, ethylene, and jasmonic acid. 6,12,13 MAPKKKs, which are the largest group compared to MAPKKs and MAPKs, function as adapters connecting the upstream signal step to the MAPK cascade.…”
mentioning
confidence: 99%
“…5,7,8 Similar studies have been conducted in several other plant species, such as rice, maize, and tomato. 10,[17][18][19] In pepper, Li et al (2012) 20 have identified 19 MPK genes and 5 MKK genes, and Iftikhar et al (2017) 10 predicted 14 MAPKs, 5 MKKs, and 60 MAPKKKs (17 in MEKK subfamily, 37 in the Raf subfamily, and 6 in the ZIK subfamily); however, information on the functional involvement of those genes, in particular MEKK subfamily genes, in response to ABA signaling and drought responses is still lacking.…”
mentioning
confidence: 99%